Rational Knowledge in The Formation of Values in National and Ethnic Groups - Akhmadiyev Nuriddin Mukhutdinovich (Indonesian Journal Publisher, 2025)
This study explores the role of rational knowledge in shaping the values of national and ethnic groups, particularly among youth in the context of globalization. The objective is to highlight how rational knowledge, alongside tradition, contributes to the preservation and development of national identity and unity. The methodology involves philosophical and sociological analysis, drawing on literature, national development strategies, and observations of youth socialization and value formation processes in Uzbekistan. The research identifies how rational thinking enables critical engagement with cultural norms, supports modernization, and strengthens civic consciousness. Key findings reveal that rational knowledge facilitates the re-evaluation and reinforcement of national values, while also cautioning against potential risks such as moral relativism and detachment from heritage. The study concludes that a balanced integration of rational knowledge and traditional wisdom is essential for fostering national cohesion and sustainable cultural development. These insights are valuable for policymakers, educators, and scholars focused on youth development and value education